Lost along the way? : Searching for the inclusion-and-difference paradigm in pharmaceutical research and regulation in Sweden - Bredström, Anna; Mulinari, Shai (Behemoth, 2025)
This article examines how the U.S. ‘inclusion-and-difference paradigm’ translates to the Swedish context. According to Steven Epstein (2007), this paradigm combines health equity arguments for racialised minorities and women with a biological understanding of racial and gender differences in medicine. Drawing on interviews with experts, policymakers, and clini- cians involved in international clinical trials in Sweden, we argue that crit- ical elements of the U.S. paradigm – notably the ‘categorical alignment’ of race-and-ethnicity taxonomies between the social worlds of medicine, gov- ernment bureaucracy, and political discourse – are absent in Sweden and, more generally, Europe. Consequently, there is no coherent framework for interpreting the existing ‘niche standardisation’ of certain medicines based on race and ethnicity, such as racialised treatment recommendations. In conclusion, we discuss possible future scenarios and highlight a recent col- laboration between the pharmaceutical industry and EU institutions. Des- pite the challenging context, this collaboration aims to establish a European standard for race and ethnicity data in clinical trials. However, we argue that such attempts warrant caution: with racism being so wide- spread in contemporary Europe, emphasising racial differences in medi- cine may unintentionally reinscribe harmful notions of race.